The butterfly genus Laothus (Lycaenidae), with the description of a new species and a morphology-based phylogenetic outline - Prieto, Carlos; Boyer, Pierre; Trujano-Ortega, Marysol; Lorenc-Brudecka, Jadwiga (Zootaxa, 2025)
The taxonomy of the genus Laothus Johnson, Kruse & Kroenlein, 1997 is revised. A new species, Laothus isakubi Prieto, sp. nov., endemic to the Sierra Nevada de Santa Marta, is described. Adults and genitalia of the new species are illustrated and compared with its closest relatives, Laothus viridicans (Felder & Felder, 1865) and Laothus cockaynei (Goodson, 1945). An updated checklist and two dichotomous keys for the identification of males and females are provided. A phylogenetic analysis based on 22 morphological characters coded for parsimony resulted in a single most parsimonious tree of 30 steps with a CI of 83 and RI of 88, in which Laothus is recovered as monophyletic.